(untitled) (Nigerian Journal of Technology, 2025)
How to render unsafe water potable is a chief priority for most governments and people. This has brought about the evolution of water treatment technologies. This article provides a review of these technologies and the criteria for selecting them, and uses the multi-criteria decision making (MCDM) approach to rank each set and select the best technology and the most important criterion. It employed two MCDM methods to quantitatively evaluate ten water treatment technologies with regard to ten criteria for selection. Data were obtained from available literature and applied to analyze the technologies and assess the effect of the criteria on them in any location under the same circumstances by pairwise comparison. The technologies were rated against the criteria on a 5-point Likert scale. The absolute values obtained were used to generate relative ones by comparing the technologies and the criteria on Saaty’s 9-point Scale of Relative Importance. Pairwise comparison matrices were formed and weighted. A global matrix was computed from which the final rankings were obtained. AHP ranked electrodialysis highest, followed by electrodialysis reversal while TOPSIS ranked ion exchange technology highest, followed by electrodialysis reversal. For the criteria, economy and efficiency were found to be the most influential while legal aspects was the least. This means that electrodialysis reversal is the best among the ranked technologies with regard to the criteria for selection considered while economy and efficiency are the most important criteria. Hence, the study proposes electrodialysis reversal for municipal, commercial and private water treatment.